Implementation of STAD Type Cooperative Learning Model Oriented on Problem Based Learning in Discrete Mathematics - Katrina Samosir (Study Program of Mathematics Education of Unimed Postgraduate Program, 2023)
The objective of study are reveal to : 1) Determine that the implementation-oriented models of cooperative learning on problem based learning can improve student learning outcomes in discrete mathematics, 2) Knowing that application of cooperative learning model which is based on problem-oriented learning can improve students’ understanding of concept of discrete mathematics, 3)Knowing that application of cooperative learning model which is based on problem-oriented learning can improve students’ understanding of proof or solving problems on discrete mathematics.The method of research used a classroom action research and that becomes the subject of research is the sixth semester students who follow a discrete mathematics 2 course.After using this strategy in cycle 1, of the achievement test showed levels mastery learning class is 81.2% with an average value of 83.9.It shows that the implementation of the Model Application Oriented Learning Cooperative Learning Problem Based on Discrete Mathematics 2 successful. It means that the learning model to improve learning outcomes of students.Application of Cooperative Learning Model Oriented Problem based Learning can improve students’ understanding of concepts and improve student’s ability to prove or solving problems on Discrete Mathematics 2. Acquired 84.9% of the students understand the concepts with an average value of 85.6% on Discrete Mathematics 2. The percentage of students understand the concept at a competent level of ability (B) or very competent (A) is only 41.36%.This is due to the performance of the student group discussion is d not optimal, because there are three aspect that the average score of more than two an less than three,namely (1) the focus and meaning of the question, (2) ability to respond to questions other groups, and (3) clarity in argued the question or comments of other groups. Required to mitigate increased frequency of exercise solve problems on the discussion group.Keywords: Cooperative Learning, STAD, Problem Based Learning, Learning Outcomes